2019
DOI: 10.1371/journal.pone.0208807
|View full text |Cite
|
Sign up to set email alerts
|

Impact of time to local recurrence on the occurrence of metastasis in breast cancer patients treated with neoadjuvant chemotherapy: A random forest survival approach

Abstract: BackgroundWe studied the relationship between time to ipsilateral breast tumor recurrence (IBTR) and distant metastasis-free survival (DMFS) in patients with breast cancer treated by neoadjuvant chemotherapy (NAC).MethodsBetween 2002 and 2012, 1199 patients with primary breast cancer were treated with NAC. Clinical, radiological and pathological data were retrieved from medical records. Multivariate analysis was performed with the random survival forest (RSF) method, to evaluate the relationship between time t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…The role of TLR on survival of a variety of cancers, including breast cancer, rectal cancer, and gastric cancer [13,[19][20][21], has long been debated, whereas there is no research on this subject in RPS. To the best of our knowledge, this is the first study to investigate the potential impact of TLR on the outcomes of patients with STS of the retroperitoneum.…”
Section: Discussionmentioning
confidence: 99%
“…The role of TLR on survival of a variety of cancers, including breast cancer, rectal cancer, and gastric cancer [13,[19][20][21], has long been debated, whereas there is no research on this subject in RPS. To the best of our knowledge, this is the first study to investigate the potential impact of TLR on the outcomes of patients with STS of the retroperitoneum.…”
Section: Discussionmentioning
confidence: 99%
“…Many computational methods have been developed to predict the survival of breast cancer patients receiving NAC treatment based on the information recorded during the clinical treatment processes. Recently, Lai et al proposed a prognostic nomogram model to predict disease-free survival (DFS) (21), Laas et al used a random survival forest method to evaluate distant metastasis-free survival (DMFS) (22), and Tahmassebic et al compared eight machine learning algorithms for the early prediction of pCR, including the support vector machine (SVM), linear discriminant analysis (LDA), extreme gradient boosting (XGBoost), where the XGBoost algorithms attained the best performance (23). The above methods achieved good prediction accuracy, and demonstrated that the computational approach is a practical contribution to evaluating NAC.…”
Section: Introductionmentioning
confidence: 99%
“…Some large-scale clinical data indicate that systemic adjuvant chemotherapy should generally not be recommended for most patients with early BC following surgery or radiotherapy, since chemotherapy would result in far greater toxicity relative to the survival benefit of the patients [ 4 6 ]. However, patients with a low likelihood of survival who do not undergo chemotherapy will quickly relapse, which results in the invasion of adjacent tissues and distant metastasis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…radiotherapy, since chemotherapy would result in far greater toxicity relative to the survival benefit of the patients [4][5][6]. However, patients with a low likelihood of survival who do not undergo chemotherapy will quickly relapse, which results in the invasion of adjacent tissues and distant metastasis [7].…”
mentioning
confidence: 99%